IDENTIFICATION AND ANALYSIS OF THE NATURE TOURISM POTENTIAL IN PARI ISLAND, THE THOUSAND ISLANDS, JAKARTA - Nadira Nur Shadrina; Qurrotu Aini Besila; Hinijati Widjaja (Universitas Trisakti, 2023)
Pari Island is one of around 110 islands in the Thousand Islands cluster that are inhabited by locals. This island with an area of 41.32 hectares contains many sorts of abundant natural resources and offers diverse tourism potentials including marine tourism, nature tourism and education. In addition to its coastal habitat, Pari Island is home to mangrove ecosystems, seagrass beds, and coral reefs, which captivate both local and international tourists. As a tourist destination, the management of nature tourism on Pari Island has not yet been completely established, therefore visitor attention is primarily centered on other tourist attractions in the Thousand Islands. The underlying issue of this research are what is the current state of nature tourism on Pari Island? Is there any further tourism potential that can be developed? The aims of the research are to assess the existing condition of nature tourism on Pari Island- both physically and in terms of management, and carry out identification of further nature tourism potentials on Pari Island. This research uses qualitative descriptive method based on a case study approach. Analysis of Operational Areas of Nature Tourism Objects and Attractions is used to define the strategy for developing Pari Island's nature tourism potential by analyzing both internal and external tourism potential. The outcomes of the research are to promote the potential of Pari Island to develop nature tourism area as a whole that incorporates all stakeholders and benefits all parties involved.